Financial health and risk in the tourism sector in Colombia (2011)
They were applied a multivariate model of health, and a risk factors analysis within an epidemiological model to the financial statements. The sample was composed of the companies in the tourism sector in Colombia, the financial variables of cash flow, profit and loss and equity ownership were used as health indicators. Scores on these indicators were normalized and used for grouping the companies into two groups (healthy and diseased) by a hierarchical cluster. They were also estimated cutoff points in other different variables on the financial statements related to the groups obtained, by optimal binning. Finally, the odds ratio and relative risk, to determine the association between the presence or absence of disease risk and financial health of companies, were obtained. This showed the existence of different variables in the financial statements, which can divide the companies into healthy and diseased, as the risk factors